Development of PAI Curriculum at Non-Formal Education Institutions (Majelis Taklim) - Dhimas Alunandika; Khozin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Majelis Taklim Masjid Ad-Din, located in Pagar Dewa urban village, Bengkulu City, needed an understanding of how to manage PAI curriculum contextually. The researcher wanted to know how the PAI curriculum of Majelis Taklim Masjid Ad-Din was developed. The study is usually conducted on Friday dawn and is always enlivened by local residents. The research method used case study-based qualitative. The results of the field research show that the lessons at Majelis Taklim Ad-Din are similar to the school curriculum, with materials selected and set for each subsequent month. However, the material given at Majelis Taklim Masjid Ad-Din each year may differ from the material given at the school each year. So that the speaker only conveys what is decided by the mosque management.